المسلك الإشاري عند المتصوفة في شرح الحديث النبوي : دراسة نقدية لنماذج مختارة - أمين، مصطفى (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims at shedding light on the Ishari method in explaining the Hadith through identifying the meaning of the Ishari method and its role in the methods of explaining the Hadith, as well as showing its most prominent features, its critical aspects, and the final decision of accepting or rejecting hadith. The researcher has adopted three methods in this research. The inductive method through collection of the scientific material from the narrations of the Prophetic Hadiths and writings on the Ishari method. The analytical approach is through the study of the scientific material. The study concluded with the definition of the Ishari method in three new ways that are consistent with the three different types, Al-Faidi which is explaining a new unintended meaning starting from the hadith, the philosophical is through the connection between the meaning of hidden in the mind of the Hadith explainer or interpreter and the apparent meaning of it through the reference and inspiration. The audio approach through matching the voice tone of the text. The researcher proved the validity of the legitimecy of the Ishari's method and its invaluable rule in authenticating the hadith.